The Effects of Financial Literacy, Self-Efficacy, and Financial Stress on Risky Credit Behav-ior of Generation Z: Evidence from Pay Later Users - Constansje, Brithania; Kurniasari, Florentina; Abubakar, Arlyana (Journal of Entrepreneurship, Business and Economics; Vol 11 No 1 (2023), 2023)
The utilization of pay later in Indonesia has increased significantly over the past year. However, not all pay-later users are aware of the negative impact that comes with the conveniences of-fered. This can be seen from the percentage level of financial literacy in Indonesia which is still lower than the level of financial inclusion. This means that many users of financial products, one of which is pay later users, have used financial products without having adequate knowledge. This study aims to determine the effect of financial literacy and self-efficacy on risky credit be-havior with financial stress as a mediator. financial literacy, financial self-efficacy, and finan-cial stress on risky credit behaviour variables. The sample of the study is Indonesian Generation Z who have used pay later. Research data was collected by conducting an online survey, where questions had to be answered by respondents by assessing one (strongly disagree) to five (strong-ly agree). In addition, this study uses the Structural Equation Model (SEM) to analyze the data that has been collected through a questionnaire. From the data analysis, it was found that the financial literacy of Generation Z has a significant positive relationship with financial self-efficacy, financial self-efficacy of Generation Z does not have a significant negative relationship with risky credit behavior, and financial literacy of Generation Z has a significant negative rela-tionship with risky credit behavior, financial self-efficacy does not mediate the relationship be-tween financial literacy and risky credit behavior, and financial stress does not moderate the relationship between financial literacy and risky credit behavior. The result of the study can be used by the financial institution to educate the Gen-Z generation about the risk financial consid-eration before making financial decision. Research paper Keywords: Financial Literacy, Financial Self-efficacy, Financial Stress, Pay Later, Risky Credit Behaviour Reference to this paper should be made as follows: Constansje, B., Kurniasari, F., & Abubakar, A. (2023). The Effects of Financial Literacy, Self-Efficacy, and Financial Stress on Risky Credit Behavior of Generation Z: Evidence from Pay Later Users. Journal of Entrepreneurship, Business and Economics , 11 (1), 180–210